Factors Associated with Midwives' Knowledge Regarding Congenital Hypothyroidism Screening and Early Neonatal Management: A Cross-Sectional Study - Anggraini, Lili; Narsiah, Narsiah; Aryati, Aryati (Chakra Brahmanda Lentera Institute, 2026)
Background: Congenital hypothyroidism is a preventable cause of intellectual disability in neonates. Although neonatal screening programs have been implemented in Indonesia, gaps in midwives’ knowledge of screening and early management may hinder timely diagnosis and referral. Evidence on factors associated with midwives’ knowledge in primary healthcare settings remains limited. This study aimed to analyse factors associated with midwives’ knowledge regarding congenital hypothyroidism screening and early neonatal management. Methods: A cross-sectional analytical study was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines among 78 midwives registered with the Indonesian Midwives Association of Indonesia Kedungwaringin Branch, Bekasi Regency, West Java, Indonesia, in 2025. Total sampling was applied. The dependent variable was knowledge level (good/fair/poor), and independent variables included age, education level, years of work experience, training attendance, and professional journal-reading habits. Data were collected using a validated questionnaire (20 items across 5 domains; Cronbach’s α = 0.82; Content Validity Index = 0.87). Bivariate analysis was performed using Chi-Square tests, reporting χ² statistics, degrees of freedom, p-values, and 95% confidence intervals. Multivariable logistic regression was additionally conducted. Results: Of 78 respondents, 44 (56.4%) had good knowledge, 25 (32.1%) fair, and 9 (11.5%) poor knowledge. The majority were aged ≥30 years (59.0%), held a Diploma III (D3) qualification (57.7%), had >5 years of work experience (62.8%), had not attended CH-related training (56.4%), and did not routinely read midwifery journals (61.5%). Statistically significant associations were found between knowledge level and age (p = 0.001, OR = 1.84, 95% CI: 1.12–3.02), education level (p = 0.002, OR = 3.76, 95% CI: 1.58–8.94), years of work experience (p = 0.001, OR = 0.27, 95% CI: 0.11–0.66), training attendance (p < 0.001, OR = 7.04, 95% CI: 2.68–18.49), and journal-reading literacy (p = 0.002, OR = 4.85, 95% CI: 1.82–12.92). Midwives with higher education and training demonstrated significantly greater odds of good knowledge. Conclusion: Strengthening continuing professional education and evidence-based literacy programs may improve the quality of congenital hypothyroidism screening and support earlier neonatal diagnosis. Targeted CH screening training programs and promotion of professional reading habits are recommended as priority interventions for primary healthcare midwifery services in Indonesia. Multicenter longitudinal and intervention studies are warranted to establish causal relationships and evaluate training program effectiveness